Mangrove Planting as a Natural Protection Measure Coastal Environment Risk Vulnerability - Rasyidi, Gunawan; Silalahi, Apolinus; Rodhianto, Imam; Ulasaswini, Andi Ade (Program Studi Kesehatan Masyarakat UIN Alauddin Makassar, 2024)
Mangroves are widely known for their role as natural protection against various environmental risks such as storms, tsunamis, waves and coastal erosion by being the first line of defense in protecting coastlines. Unfortunately, in many parts of the world, mangrove forests have been lost due to the pressures of urban development, the rapid expansion of aquaculture and agriculture, mining, overexploitation of timber, and increasing environmental risks. This activity aims to assess mangrove planting as a natural protection measure for the risk vulnerability of the coastal environment. The target of this service activity is the coastal area of Tongo Village. The results of service activities show that the mangroves planted on the coast of Tongo Village, namely Rhizophora Sp and Ceriops Sp grow well. It will take at least another five years to assess its effectiveness in mitigating coastal erosion. Planting mangroves in coastal areas is very important in an effort to protect the natural risk vulnerability of the coastal environment. This is important to do as soon as possible because the growth of mangrove plants requires a long time to get maximum benefits.